Study of Steel Slag Filter Unit as a Secondary Treatment System for Removing Total Phosphorus from Textile Industry Wastewater - Mohd Arshad, Nur Ain Nazirah; Hamdan, R. (International Journal of Integrated Engineering, 2021)
Eutrophication is one of the global concerned due to algae bloom in the natural surface water such as lakes and swamp area. Industrial effluent with incomplete treatment discharged has become one of the main culprits to this phenomenon. Approximately, 0.3 – 13 mg/L of total phosphorus can be found in the final discharge of industrial effluent showing that the existing treatment including an activated carbon filter (ACF) has limitation in polishing the phosphorus. Therefore, this 16 week of study has been designed to study the alternative treatment phosphorus removal at secondary stage to replace the tertiary treatment by using steel manufacturing by-product as filter media for effective phosphorus removal from the textile industry wastewater. Two units of lab-scale vertical steel slag filter (SSF) systems under aerated and unaerated conditions have been developed for this study. The samples were collected and analysed biweekly for selected parameters including pH, alkalinity, DO and TP. The results obtained from this study show that the unaerated steel slag filter has a high efficiency of TP removal which ranged from 46% to 70% compared to the aerated SSF with removal efficiency ranged from 37% to 66%. Besides, the existing ACF removal efficiency was ranged from 36% to 54%. Thus, the use of steel slag in removing phosphorus from textile wastewater is possible with the used of both aerated and unaerated steel slag filter systems. Furthermore, the removal mechanism involved was likely to be precipitation and adsorption.